Estimation of White Trevally (Decapterus macrosoma) Stock in the Waters of Nusa Laut, Maluku, Indonesia - Habib Harlino Rofi Latuconsina; Imanuel Villian Trayanta Soukotta; Fahrul Rozy Fakaubun; Wildan Tino; Milyan Uli Latue; Muhammad Fahrul Barcinta; Domey Moniharapon (Politeknik Negeri Sambas, 2026)
The potential of marine resources from the Banda Sea, particularly the waters of Nusa Laut, represents an important economic aspect for local fishers. Several fishing fleets targeting scad, including mini purse seine vessels, are widely distributed in the area, with continuous exploitation activities occurring every week. This study aimed to analyze the growth pattern, mortality, and sex ratio of white scad (Decapterus macrosoma) in Nusa Laut waters, landed at Arumbai Market, Ambon. The research was conducted using a survey method from January to June 2025, with a total sample of 150 individuals. Data were analyzed based on growth pattern, fish mortality, and sex ratio analyses. The results showed that the asymptotic length (L∞) was estimated at 24.7 cm total length (TL), with a growth coefficient (K) of 0.61 year⁻¹ and a theoretical age at zero length (t₀) of −0.25 year. The fishing mortality (F) value was 0.46 year⁻¹, the total mortality (Z) was 1.80 year⁻¹, and the natural mortality (M) was 1.34 year⁻¹, resulting in an exploitation rate (E) of 0.25. The sex ratio analysis conducted from February to June indicated that the proportion of male and female fish was in a balanced condition, with a ratio of 1:1. Based on the exploitation analysis, the length corresponding to half of the asymptotic length (L∞/2 = 12.35 cm TL) indicated that the captured fish were still relatively small. Therefore, the biological characteristics of white scad caught in Nusa Laut waters, Central Maluku, and landed at Arumbai Market, Ambon City, indicate that the fish are predominantly captured at a small size with a relatively low exploitation level.